Hidden Administrative Infractions: Conceptualization and Application of the Statute of Limitations to Determine Liability - Patroni Vizquerra, Ursula (2025)
This paper proposes the incorporation of the legal concept of the hidden administrative infraction into administrative law, based on an analysis of the deliberate conduct of the alleged offender aimed at concealing or disguising an administrative infraction through one or more unlawful acts or omissions. From this perspective, a new conceptualization of administrative infractions is proposed, one that considers not only the infringing conduct but also the actions intended to hide it. This approach addresses the issue of the statute of limitations for administrative infractions, preventing offenders from evading or hindering the exercise of sanctioning authority, and thus escaping punishment, through illicit maneuvers.